GENETIC DIVERSITY OF ONE CULTIVAR AND 29 GENOTYPES OF TOBACCO BASED ON MORPHOLOGICAL AND YIELD PROPERTIES - M. Camlica; G. Yaldiz (Journal of Animal and Plant Sciences, 2020)
Tobacco (Nicotiana tabacum) is one of the cash and industrial crops commonly grown throughout the world. This plant is important for the agriculture sector in Turkey, with high-quality varieties being produced in different regions of the country. This study aimed to examine important morphological properties and yield of a cultivar and some genotypes of tobacco under the conditions of Bolu province in Turkey in 2015 and 2016. Genetic variability parameters such as GCV (%), PCV (%), GA and heritability were conducted to provide the best image of the tobacco cultivar and genotypes. GCV values were near to PCV values for the properties like DFT, DT and OV indicative high contribution of genotypic effect for phenotypic expression of such properties. These properties had moderately high heritability with 79.98%, 73.95% and 79.51%, respectively. The highest fresh leaf weight was observed in the AR-1 cultivar (525.0 kg da-1) and ESR-7 genotype (646.30 kg da-1) in the first year and BSR-3 (358.22 kg da-1) and ESR-6 (320.19 kg da-1) genotypes in the second year. A correlation analysis was also conducted between these traits of tobaccos. Highly significant and positive correlations were found between DFT-DT, LL-LW and FLW-DLW. A dendrogram was constructed to determine the relationships between the investigated plants based on morphological properties and yield values. One cultivar and 29 genotypes were located in two main groups as A (14 genotypes and one cultivar) and B (15 genotypes). The genotypes included same region were located in different groups.
Keywords: Cash crop; correlation analysis; dendrogram; industrial plant; Nicotiana tabacum